Comunidad. Hacia una teoría latinoamericana del comparatismo - Link, Daniel (Universidad Nacional del Litoral, 2014)
The examination of the vast work of Alfonso Reyes (Monterrey, 1889 – Mexico City, 1959), essential in the performance of Latin American comparative studies, illuminate the more general difficulties of the comparativism when it is still intended to reflect on their purpose, solve its crisis and propose an analytical method, specially with respect to overcoming its remains of positivism. Reyes’s comparatism contests parallels, similarities and influences, because their research is located in the «People’s mentality and imagination» level, the living conscience of a formless propagation.